2011
DOI: 10.1093/infdis/jir219
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Mouse Model to Establish Tropheryma whipplei as a Diarrheal Agent

Abstract: Tropheryma whipplei has long been considered as a rare bacterium causing a rare disease, Whipple's disease. However, recent advances now suggest that T. whipplei is a ubiquitous environmental bacterium that may cause gastroenteritis, commonly associated with viral pathogens. We developed an animal model to support this hypothesis. We found that orally given T. whipplei induced diarrhea in mice, without spreading into the intestines. Aggravating factors, such as damage to the intestinal mucosa, favored bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…In France, T. whipplei has recently been identified as an agent of gastroenteritis in young children, either alone or in combination with other pathogens [10] . In parallel, an in vivo model of infection with T. whipplei in mice was developed that further confirmed the role of T. whipplei as an agent of gastroenteritis [24] . In our study, the analysis of children who were between 5 and 10 years old confirms a link between T. whipplei and gastroenteritis, although the interpretation of the results from the 4-year-old and younger group is more difficult.…”
Section: Discussionmentioning
confidence: 79%
“…In France, T. whipplei has recently been identified as an agent of gastroenteritis in young children, either alone or in combination with other pathogens [10] . In parallel, an in vivo model of infection with T. whipplei in mice was developed that further confirmed the role of T. whipplei as an agent of gastroenteritis [24] . In our study, the analysis of children who were between 5 and 10 years old confirms a link between T. whipplei and gastroenteritis, although the interpretation of the results from the 4-year-old and younger group is more difficult.…”
Section: Discussionmentioning
confidence: 79%
“…8 The development of an animal model of pneumonia induced by T. whipplei will allow us to investigate whether all of Koch's postulates are fulfilled as for T. whipplei in gastroenteritis. 14 The milestones of the arguments allowing the implication of T. whipplei as an agent of pneumonia are summarized in a supplementary Table. The genotype 11 detected in our patient has been previously observed in France, Germany and Switzerland in various circumstances, such as classic Whipple's disease, chronic carriage, and localized spondylodiscitis. 12 On the whole, the recognized spectrum of T. whipplei infections is still increasing, and we believe that pneumonia due to T. whipplei, as well as gastroenteritis, whose role was also shown in an experimental model, belongs to the spectrum of infections that are relatively common.…”
Section: Discussionmentioning
confidence: 99%
“…Sulis et al [17] have reported a case of TW in which no specific risk factors for opportunistic infections were identified in patients with candidal esophagitis except TW infection; therefore, they hypothesized that the candidal infection was directly related to WD. Moussawi et al [18] have proved using a mouse model that TW alone cannot invade tissues but can smolder in cells, including macrophages, by inhibiting the xenogenic phagocytosis process, a selective autophagy that targets pathogens. Some macrophages appear to play a role in limiting the invasion of fungi on mucosal surfaces [19]; Therefore, the peripheral flagellates and Candida sp.…”
Section: Immunoreactivity and Periodic Acid-schiffmentioning
confidence: 99%